Duración e intensidad de la puesta y su dependencia del tamaño corporal: El caso del bonito Euthynnus alletteratus capturado en el suroeste del Golfo de México - Cruz-Castán, Roberto; Meiners-Mandujano, César; Curiel-Ramírez, Sergio (Revista de Biología Marina y Oceanografía, 2019)
In terms of fish dynamic population, reproduction is a process related with corporal size of each population member, which is tied with the spawning time and number of eggs produced. In order to relate the size of female little tuny (Euthynnus alletteratus), located in the southwest Gulf of Mexico, and its contribution in reproductive process, cycle and reproductive characteristics were analyzed by different size groups. Biological data were obtained by the artisanal fishing fleet of Antón Lizardo Veracruz community (Mexico). A total of 480 fish were caught from December 2009 to November 2012. Size structure, gonadosomatic index and duration and intensity spawning index (IDI) were determined. The gonadosomatic index showed a decrease in the population after April and July. Nevertheless, these months and the fraction of spawning female may vary depending on size groups. According with the IDI, the individuals with the highest contribution in reproductive process belong to sizes from 44 to 56 cm. Therefore, in order to guarantee the conservation of this species, it is imperative to mainly direct the management measures towards the females from these sizes.